A quasi-experimental study on the use of pop-up books to improve dental caries knowledge among elementary school students - Faradiza, Awa Mumtaza; Dewi, Maria Ulfah Kurnia; Sholekhah, Nur Khamilatusy (Universitas Padjadjaran, 2025)
ABSTRACTIntroduction: Dental caries are caused by multiple factors, including both internal and external influences on individuals. The Kedungmundu Health Center area ranks first in the prevalence of dental caries among elementary school students, with 3.739 affected children. If left untreated, caries can lead to infection, spread to other teeth, and negatively affect overall oral health. This study aims to analyze the effectiveness of pop-up books in improving dental caries knowledge among elementary school students. Methods: This study employed a quasi-experimental design using a pre-post control group approach. The sample consisted of 66 students aged 10-11 years from SDN Sendangmulyo 01 Semarang, selected through simple random sampling. The participants were divided into two groups 33 in the experimental group and 33 in the control group. Statistical analysis was performed using a paired t-test. Results: Prior to the intervention, a majority of control participants (81.8%) and experimental participants (57.6%) displayed good understanding of dental caries. Following the counseling session, the experimental group exhibited significant improvement, with 81.8% attaining good knowledge compared to 60.6% in the control group. Statistical analysis revealed significant knowledge gains in the experimental group (p=0.006), confirming pop-up book media as an effective educational tool. Conclusion: Educational counseling using pop-up book media is effective in increasing dental caries knowledge among elementary school students.KEYWORDSSchool age children, dental health education, pop-up books